Sodium secondary battery electrolyte and sodium secondary battery
By using a combination of organic solvents, electrolyte sodium salts and specific fluorine-containing additives in the sodium secondary battery electrolyte, the problem of irreversible decomposition reaction of sodium ion battery electrolyte is solved, and the cycle stability and coulomb efficiency of the battery are significantly improved.
Patent Information
- Application Number
- CN202111575711.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-12-21
AI Technical Summary
The electrolyte of sodium ion batteries is prone to irreversible decomposition reactions at low potentials, resulting in a decrease in battery cycle stability and Coulomb efficiency. The existing electrolyte additives perform poorly in the sodium system, and even cause battery performance to decline.
Using a sodium secondary battery electrolyte containing organic solvents, electrolyte sodium salts and specific fluorine-containing additives, the synergistic effect of these components reduces the irreversible decomposition reaction of the electrolyte and improves the circulation stability and capacity retention rate of the electrolyte. and Coulomb efficiency.
It significantly improves the cycle stability and Coulomb efficiency of sodium secondary batteries, reduces the increase in acidity and chromaticity of the electrolyte, extends the cycle life of the battery, and improves the stability of the battery at different magnifications.
Smart Images

Figure CN114156539B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium batteries, and in particular to a sodium secondary battery electrolyte and a sodium secondary battery. Background Art
[0002] Lithium-ion batteries have become the first choice for digital products, hybrid electric vehicles, pure electric vehicles, and grid energy storage due to their high capacity, good cycle stability, and low pollution, and were industrialized in the 1990s. However, after 30 years of development, the limited and extremely unevenly distributed lithium resources have been consumed in large quantities. At present, the market demand for lithium-ion batteries is still growing year by year, and the recycling technology of lithium-containing compounds has far failed to keep up with the pace of lithium resource consumption, which ultimately caused the price of raw materials such as lithium carbonate to rise.
[0003] Although the energy density of sodium-ion batteries is slightly inferior to that of lithium-ion batteries, they have developed rapidly in recent years due to their similar working mechanism and abundant and evenly distributed raw materials. They have achieved initial industrialization in 2021. Sodium-ion batteries are expected to gradually replace traditional lead-acid batteries, and are also expected to try lithium-sodium sharing in the field of electric vehicles and be fully applied in large-scale energy storage devices.
[0004] Since the sodium-ion battery electrolyte does not directly determine the energy density of the battery, its research progress is far behind that of the positive and negative electrode materials. As the commercialization of sodium-ion batteries becomes clearer, the electrolyte as an ion-conducting carrier will also become a new research hotspot. Similar to lithium-ion batteries, sodium-based electrolytes will also undergo reduction and decomposition, and the reduction and decomposition phenomenon of sodium-based electrolytes is more severe, mainly manifested as follows: carbonate solvents undergo reduction and decomposition at low potentials to produce obvious dendritic decomposition products, which cover the surface of hard carbon particles, reducing the effective surface area of hard carbon particles and seriously affecting the transmission of sodium ions on the hard carbon surface; battery impedance increases significantly after multiple cycles, and battery cycle stability and coulombic efficiency decrease.
[0005] In a full battery, it is important to inhibit the reduction and decomposition of the electrolyte. The decomposition of the electrolyte causes irreversible loss of active sodium in the system, resulting in a decrease in the cycle life of the full battery. At the same time, the resulting large impedance may lead to safety issues such as thermal runaway. Therefore, the design and optimization of the electrolyte is one of the key factors to ensure battery performance.
[0006] The theoretical basis of lithium-ion batteries shows that electrolyte is the key to building a good solid-liquid interface, and one of the measures to balance performance and economic benefits is to use electrolyte additives. Although electrolyte additives have been widely used in industrial lithium-ion batteries, similar research progress in the sodium system is very limited. Current research also shows that the same additives applied to sodium-ion batteries may not necessarily show an ideal improvement effect. Even some commercial lithium-ion battery additives produce obvious harmful side reactions in the sodium system or cause battery performance degradation. For example, the work reported by the Komab team in 2011 showed that adding a trace amount of VC to the carbonate-based electrolyte will also cause the electrolyte to change color significantly. The cycle stability and capacity of the sodium-ion battery using this electrolyte are significantly lower than those of the basic electrolyte, which indicates that the introduction of VC may be accompanied by harmful side reactions; DFEC and ES lead to battery cycle performance degradation. In addition, the Ponrouch team found that in the EC / PC system, the introduction of the additive FEC will lead to a decrease in the sodium storage performance of hard carbon, which is manifested as a decrease in capacity and coulombic efficiency.
[0007] The experimental results reported above indicate that sodium-ion batteries may have different film-forming rules from lithium-ion batteries, and the same additives may also play different roles in lithium and sodium systems. This fully demonstrates that the development of sodium-ion battery additives is not a simple replication of the lithium system. On the contrary, the exploration of sodium-ion battery additives is more challenging than that of the mature lithium system. Therefore, research on additives in the field of sodium-ion batteries requires more attempts and deeper analysis. Summary of the invention
[0008] Based on this, the present invention provides a sodium secondary battery electrolyte with less irreversible decomposition reaction, good cycle stability, high capacity retention rate and high coulombic efficiency, which can be used to prepare a sodium secondary battery with good cycle performance and low impedance.
[0009] The technical solution is as follows:
[0010] A sodium secondary battery electrolyte, comprising an organic solvent, an electrolyte sodium salt and a fluorine-containing additive having a structure represented by formula (I);
[0011]
[0012] in:
[0013] R1, R2, R3, R4 and R5 are independently selected from -H, halogen, C1-C 20 Alkyl, halogenated C1~C 20 Alkyl, C6~C 26 Aryl or halogenated C6~C 26 Aryl.
[0014] In one embodiment, R1, R2, R3, R4 and R5 are independently selected from -H, F, Cl-C 10 Alkyl, F-substituted C1~C 10 Alkyl, C6~C 12 Aryl or F-substituted C6~C 12 Aryl.
[0015] In one embodiment, R1, R2, R3, R4 and R5 are independently selected from -H, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 1-pentyl, 2-pentyl, 3-pentyl, 1-hexyl, 2-hexyl, 3-hexyl, octyl, phenyl, naphthyl or biphenyl.
[0016] In one embodiment, the fluorine-containing additive has a structure as shown in any one of the following (F1)-(F8):
[0017]
[0018]
[0019] In one embodiment, the fluorine-containing additive is
[0020] In one embodiment, the sodium secondary battery electrolyte comprises, by mass percentage of the sodium secondary battery electrolyte, 72% to 92% of an organic solvent, 7% to 23% of an electrolyte sodium salt, and 1% to 5% of a fluorine-containing additive having a structure represented by formula (I).
[0021] In one embodiment, the sodium secondary battery electrolyte comprises, by mass percentage of the sodium secondary battery electrolyte, 79% to 90% of an organic solvent, 9% to 20% of an electrolyte sodium salt, and 1% to 3% of a fluorine-containing additive having a structure represented by formula (I).
[0022] In one embodiment, the organic solvent is a cyclic carbonate or a linear carbonate, or a mixed solvent consisting of a cyclic carbonate and a linear carbonate.
[0023] In one embodiment, the cyclic carbonate is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-hydroxybutyrolactone (GBL), 4-hydroxyvalerolactone (GVL) and δ-valerolactone (DVL);
[0024] The linear carbonate is selected from at least one of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0025] In one embodiment, in the mixed solvent, the volume ratio of the cyclic carbonate to the linear carbonate is (0.8-1.2):1.
[0026] In one embodiment, the organic solvent is a mixed solvent consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1; or
[0027] The organic solvent is a mixed solvent consisting of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1; or
[0028] The organic solvent is a mixed solvent consisting of gamma-hydroxybutyrolactone and diethyl carbonate in a volume ratio of 1:1.
[0029] In one embodiment, the electrolyte sodium salt is selected from at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSA / NaFSI), (trifluoromethylsulfonyl)imide (NaTFSI) and sodium trifluoromethylsulfonate (NaOTF).
[0030] In one embodiment, the concentration of the electrolyte sodium salt in the organic solvent is 0.8 mol / L to 1.5 mol / L.
[0031] The present invention also provides a sodium secondary battery, comprising the sodium secondary battery electrolyte as described above.
[0032] In one embodiment, the sodium secondary battery is a sodium ion battery or a sodium air battery.
[0033] In one embodiment, the sodium ion battery is a hard carbon / sodium half-cell, a sodium / sodium symmetric battery, or a sodium vanadium phosphate / hard carbon full battery.
[0034] The present invention has the following beneficial effects:
[0035] The electrolyte provided by the present invention comprises an organic solvent, an electrolyte sodium salt and a specific fluorine-containing compound having a structure shown in formula (I). Through the synergistic effect of the three, the irreversible decomposition reaction of the electrolyte can be reduced, the cycle stability, capacity retention rate and coulomb efficiency of the electrolyte can be significantly improved, and the increase of the acidity and chromaticity of the electrolyte can be significantly inhibited.
[0036] The electrolyte of the present invention is applied to sodium secondary batteries. (1) It can induce the formation of a stable, low-impedance passivation film on the electrode surface, modify the electrode interface, and the optimization of the electrode interface further promotes the improvement of the battery's cycle performance, so that the battery impedance after different cycles is greatly reduced, and the battery's rate stability and capacity are normalized, especially the hard carbon / sodium half-cell. (2) It reduces side reactions such as irreversible decomposition of the electrolyte, reduces the interface impedance, and significantly improves the interface stability, so that the capacity decay of the battery at room temperature is effectively controlled, and the cycle stability is significantly improved, especially the hard carbon / sodium half-cell. (3) It can promote more uniform sodium plating and stripping on the surface of sodium metal, achieve a more ideal modification effect on the surface of sodium metal, and ultimately stabilize the change of sodium metal overpotential, thereby improving the battery's cycle stability. This experimental result has a certain reference value for the design and optimization of sodium metal battery electrolytes. (4) The contact angle between the sodium secondary electrolyte of the present invention and the electrode (especially the hard carbon electrode) is smaller, which can achieve better wetting of the electrolyte on the surface of the hard carbon electrode. The good wettability ensures sufficient contact between the sodium secondary battery electrolyte and the electrode, thereby ensuring effective sodium ion transmission and better film formation on the electrode surface, and ultimately ensuring a reversible sodium ion insertion and extraction process and significantly improved electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 (a) is a comparison chart of the cycle stability of the hard carbon / sodium half-cells prepared in Example 1, Example 2 and Comparative Example 1 of the present invention, Figure 1 (b) is the corresponding Coulomb efficiency comparison diagram;
[0038] Figure 2 is a comparison diagram of the impedance of the hard carbon / sodium half-cells prepared in Example 1 of the present invention and Comparative Example 1 after different number of cycles;
[0039] Figure 3 It is a comparison chart of the contact angle test results of the electrolytes prepared in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0040] Figure 4 This is a comparison chart of the cycle stability of sodium vanadium phosphate / hard carbon full batteries prepared in Example 3 of the present invention and Comparative Example 2 at different rates;
[0041] Figure 5 It is a comparison chart of the cycle stability of the sodium / sodium symmetric battery prepared in Example 4 of the present invention and Comparative Example 3. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] the term
[0045] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0046] The term "alkyl" refers to a saturated hydrocarbon containing primary (normal) carbon atoms, or secondary carbon atoms, or tertiary carbon atoms, or quaternary carbon atoms, or a combination thereof. Phrases containing this term, such as "C 1-16"Alkyl" refers to an alkyl group containing 1 to 16 carbon atoms. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s -Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3- Methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH 3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).
[0047] "Aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom. It can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "C6-C 26 The term "aryl" refers to an aromatic group containing 6 to 26 carbon atoms, and suitable examples include, but are not limited to, benzene, biphenyl, naphthalene, anthracene, and phenanthrene.
[0048] "Halogen" or "halo" refers to F, Cl, Br or I.
[0049] Based on this, the present invention provides a sodium secondary battery electrolyte with less irreversible decomposition reaction, good cycle stability, high capacity retention rate and high coulombic efficiency.
[0050] The technical solution is as follows:
[0051] A sodium secondary battery electrolyte, comprising an organic solvent, an electrolyte sodium salt and a fluorine-containing additive having a structure represented by formula (I);
[0052]
[0053] in:
[0054] R1, R2, R3, R4 and R5 are independently selected from -H, halogen, C1-C 20 Alkyl, halogenated C1~C 20 Alkyl, C6~C 26 Aryl or halogenated C6~C 26 Aryl.
[0055] The electrolyte provided by the present invention comprises an organic solvent, an electrolyte sodium salt and a specific fluorine-containing compound having a structure shown in formula (I). Through the synergistic effect of the three, the irreversible decomposition reaction of the electrolyte can be reduced, the cycle stability, capacity retention rate and coulomb efficiency of the electrolyte can be significantly improved, and the increase of the acidity and chromaticity of the electrolyte can be significantly inhibited.
[0056] In one embodiment, R1, R2, R3, R4 and R5 are independently selected from -H, F, Cl-C 10 Alkyl, F-substituted C1~C 10 Alkyl, C6~C 12 Aryl or F-substituted C6~C 12 Aryl.
[0057] In one embodiment, R1, R2, R3, R4 and R5 are independently selected from -H, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 1-pentyl, 2-pentyl, 3-pentyl, 1-hexyl, 2-hexyl, 3-hexyl, octyl, phenyl, naphthyl or biphenyl.
[0058] In one embodiment, the fluorine-containing additive has a structure as shown in any one of the following (F1)-(F8):
[0059]
[0060]
[0061] In one embodiment, the fluorine-containing additive is
[0062] In one embodiment, the sodium secondary battery electrolyte comprises, by mass percentage of the sodium secondary battery electrolyte, 72% to 92% of an organic solvent, 7% to 23% of an electrolyte sodium salt, and 1% to 5% of a fluorine-containing additive having a structure represented by formula (I).
[0063] In one embodiment, the sodium secondary battery electrolyte comprises, by mass percentage of the sodium secondary battery electrolyte, 79% to 90% of an organic solvent, 9% to 20% of an electrolyte sodium salt, and 1% to 3% of a fluorine-containing additive having a structure represented by formula (I).
[0064] In one embodiment, the organic solvent is a cyclic carbonate or a linear carbonate, or a mixed solvent consisting of a cyclic carbonate and a linear carbonate.
[0065] In one embodiment, the cyclic carbonate is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-hydroxybutyrolactone (GBL), 4-hydroxyvalerolactone (GVL) and δ-valerolactone (DVL);
[0066] The linear carbonate is selected from at least one of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0067] In one embodiment, in the mixed solvent, the volume ratio of the cyclic carbonate to the linear carbonate is (0.8-1.2):1.
[0068] In one embodiment, the organic solvent is a mixed solvent consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.
[0069] In one embodiment, the organic solvent is a mixed solvent consisting of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1.
[0070] In one embodiment, the organic solvent is a mixed solvent consisting of γ-hydroxybutyrolactone and diethyl carbonate in a volume ratio of 1:1.
[0071] In one embodiment, the electrolyte sodium salt is selected from at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSA / NaFSI), (trifluoromethylsulfonyl)imide (NaTFSI) and sodium trifluoromethylsulfonate (NaOTF).
[0072] In one embodiment, the concentration of the electrolyte sodium salt in the organic solvent is 0.8 mol / L to 1.5 mol / L.
[0073] Preferably, the purity of sodium hexafluorophosphate is ≥ 99% to ensure that it can be completely dissolved in the organic solvent; further, the concentration of sodium hexafluorophosphate in the organic solvent is 1 mol L -1 .
[0074] The present invention also provides a sodium secondary battery, comprising the sodium secondary battery electrolyte as described above.
[0075] In one embodiment, the sodium secondary battery is a sodium ion battery or a sodium air battery.
[0076] In one embodiment, the sodium ion battery is a hard carbon / sodium half-cell, a sodium / sodium symmetric battery, or a sodium vanadium phosphate / hard carbon full battery.
[0077] The electrolyte of the present invention is applied to sodium secondary batteries. (1) It can induce the formation of a stable, low-impedance passivation film on the electrode surface, modify the electrode interface, and the optimization of the electrode interface further promotes the improvement of the battery's cycle performance, so that the battery impedance after different cycles is greatly reduced, and the battery's rate stability and capacity utilization are normalized, especially hard carbon / sodium half-cells. (2) It reduces side reactions such as irreversible decomposition of the electrolyte, reduces the interface impedance, and significantly improves the interface stability, so that the capacity decay of the hard battery at room temperature is effectively controlled, and the cycle stability is significantly improved, especially hard carbon / sodium half-cells. (3) It can promote more uniform sodium plating and stripping on the surface of sodium metal, achieve a more ideal modification effect on the surface of sodium metal, and ultimately stabilize the change of sodium metal overpotential, thereby improving the battery's cycle stability. This experimental result has a certain reference value for the design and optimization of sodium metal battery electrolytes. (4) The contact angle between the sodium secondary electrolyte of the present invention and the electrode (especially the hard carbon electrode) is smaller, which can achieve better wetting of the electrolyte on the surface of the hard carbon electrode. The good wettability ensures sufficient contact between the sodium secondary battery electrolyte and the electrode, thereby ensuring effective sodium ion transmission and better film formation on the electrode surface, and ultimately ensuring a reversible sodium ion insertion and extraction process and significantly improved electrochemical performance.
[0078] Specific embodiments are listed below to further illustrate the present invention in detail.
[0079] (1) The basic electrolyte and the electrolyte containing 1 wt% and 3 wt% of additives in the following examples and comparative examples are sealed in polytetrafluoroethylene containers;
[0080] (2) The amount of sodium secondary battery electrolyte used in the contact angle test is 0.2 mL to 0.5 mL. It is sealed in an inert container before the test and ensured to be sealed. The test objects are hard carbon electrodes and sodium secondary electrolytes. During the test, a 1 mL range syringe is used to add drops of liquid, and the POWEREACH contact angle meter is used for testing, and the contact angle value is analyzed by the instrument;
[0081] (3) The steps of preparing the hard carbon electrode are as follows: using a ball mill to make a slurry, the adhesive used is polyvinylidene fluoride (PVDF), the conductive agent used is Super P, the solvent used is N-methylpyrrolidone, and the ball milling time is 5 to 10 hours; the slurry is coated on a copper foil with a coating thickness of 50 μm; first, the solvent is removed by drying in an 80°C forced air drying oven for 2 hours, and then transferred to a 120°C vacuum drying oven for deep drying for 12 to 20 hours;
[0082] (4) The steps of preparing sodium vanadium phosphate electrode are as follows: using a ball mill to make slurry, the adhesive used is polyvinylidene fluoride (PVDF), the conductive agent used is Super P, the solvent used is N-methylpyrrolidone, and the ball milling time is 5 to 10 hours; the slurry is coated on aluminum foil with a coating thickness of 100 μm; first, the solvent is removed by drying in an 80°C forced air drying oven for 2 hours, and then transferred to a 120°C vacuum drying oven for deep drying for 12 to 20 hours;
[0083] (5) The steps for preparing a hard carbon / sodium half-cell are as follows: place the negative electrode shell, spring sheet, steel gasket, and metal sodium sheet in order, then drip 100 μL of electrolyte, place a glass fiber diaphragm, drip 100 μL of electrolyte, place the hard carbon electrode and the positive electrode shell in order, ensure that the centers of all parts are aligned, and press them with a battery packaging machine; wherein, the hard carbon / sodium half-cell uses a 2032 model battery shell, the hard carbon electrode has a diameter of 12 mm, the sodium sheet diameter is kept consistent with the steel gasket (15.6 mm), and the diameter of the diaphragm used is 18 mm;
[0084] (6) The steps of preparing a sodium vanadium phosphate / hard carbon full battery are as follows: place the negative electrode shell, spring sheet, steel gasket, and hard carbon electrode in order, then drip 40 μL of electrolyte, place the polymer diaphragm, drip 40 μL of electrolyte, place the sodium vanadium phosphate electrode and the positive electrode shell in order, ensure that the centers of all parts are aligned, and press with a battery packaging machine; wherein, the sodium vanadium phosphate / hard carbon full battery uses a 2025 model battery shell, the hard carbon electrode has a diameter of 12 mm, and the diaphragm used has a diameter of 18 mm;
[0085] (7) The steps of preparing a sodium / sodium symmetric battery are as follows: placing a negative electrode shell, a spring sheet, a steel gasket, and a metal sodium sheet in order, then dropping 100 μL of electrolyte, placing a glass fiber separator, dropping 100 μL of electrolyte, placing a metal sodium sheet, a steel gasket, and a positive electrode shell in order, ensuring that the centers of all parts are aligned, and pressing with a battery packaging machine; wherein, the sodium / sodium symmetric battery uses a 2032 model battery shell, the diameter of the sodium sheet is kept consistent with that of the steel gasket (15.6 mm), and the diameter of the separator used is 18 mm;
[0086] (8) The present invention performs a constant current charge and discharge test on a battery as follows: The present invention uses a blue electric tester to perform a constant current charge and discharge test. For a hard carbon / sodium half-cell, a 0.1C activation step of 3 cycles and a 0.5C cycle of 500 cycles are used, and the charge and discharge potential window is 0.01 to 2.5 V; for a sodium vanadium phosphate / hard carbon full cell, a 1C rate cycle of 500 cycles is used, and the charge and discharge potential window is 1.5 to 3.70 V; for a sodium / sodium symmetrical cell, a 0.5 mA cm -2 The current density (equivalent to the actual current 0.943mA) is constant current charging and discharging for one hour respectively, and the cycle is about 150 times (about 300 hours).
[0087] (9) The present invention performs impedance testing on hard carbon / sodium batteries that have been cycled to a certain number of times as follows: the object of the impedance test is a hard carbon / sodium half-cell that has been cycled for 150 and 500 times and is in a de-sodiumized state, and the frequency range used in the test is 100000 Hz to 0.005 Hz.
[0088] (10) The characterization method of the hard carbon electrode of the present invention is as follows: the hard carbon / sodium battery after the cycle is completed is disassembled, diethyl carbonate (DEC) is used to rinse the hard carbon electrode taken out of the disassembled battery, the residual glass fiber on the surface of the electrode is scraped off with a thin blade, and the electrode is dried for 2 to 3 hours to allow the DEC solvent on the surface of the electrode to evaporate completely, and then the electrode is sealed and stored in a 10 mL centrifuge tube for characterization.
[0089] Example 1
[0090] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0091] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0092] It is composed of 86% organic solvent, 13% electrolyte sodium salt and 1% fluorine-containing additive;
[0093] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0094] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0095] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0096] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0097] 3) Add additive F1 to the basic electrolyte obtained in step 2) with a mass fraction of 1 wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 1 wt% F1.
[0098] 4) Assembling a hard carbon / sodium button cell with the sodium secondary battery electrolyte containing 1 wt% F1 obtained in step 3), and performing a constant current charge and discharge test at a rate of 0.5C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0099] 5) Performing an AC impedance test on the battery that has been cycled to a certain number of times in step 4) to evaluate the effect of the sodium secondary battery electrolyte containing 1 wt % F1 on the battery impedance.
[0100] 6) Conducting a contact angle test on the sodium secondary battery electrolyte containing 1 wt% F1 obtained in step 3) to test the contact angle between the sodium secondary battery electrolyte and the hard carbon electrode. The size of the contact angle can reflect the wettability of the electrolyte on the surface of the hard carbon electrode.
[0101] Example 2
[0102] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0103] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0104] It is composed of 80% organic solvent, 17% electrolyte sodium salt and 3% fluorine-containing additive;
[0105] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0106] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0107] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0108] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0109] 3) Add additives to the basic electrolyte obtained in step 2) Its mass fraction is 3wt% of the total mass of the electrolyte. The solution is shaken or stirred evenly until the additive is completely dissolved and then left to stand for 12 hours to obtain a sodium secondary battery electrolyte containing 3wt% F1.
[0110] 4) Assembling a hard carbon / sodium button cell with the sodium secondary battery electrolyte containing 3 wt % F1 obtained in step 3), and performing a constant current charge and discharge test at a rate of 0.5 C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0111] 5) Conducting a contact angle test on the sodium secondary battery electrolyte containing 3 wt % F1 obtained in step 3) to test the contact angle between the sodium secondary battery electrolyte and the hard carbon electrode. The size of the contact angle can reflect the wettability of the electrolyte on the surface of the hard carbon electrode.
[0112] Example 3
[0113] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0114] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0115] It is composed of 86% organic solvent, 13% electrolyte sodium salt and 1% fluorine-containing additive;
[0116] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0117] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0118] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0119] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0120] 3) Add additive F1 to the basic electrolyte obtained in step 2) with a mass fraction of 1 wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 1 wt% F1.
[0121] 4) Assembling sodium vanadium phosphate / hard carbon button cells with the sodium secondary battery electrolyte containing 1 wt% F1 obtained in step 3), and performing constant current charge and discharge tests at a rate of 0.1C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0122] Example 4
[0123] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0124] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0125] It is composed of 86% organic solvent, 13% electrolyte sodium salt and 1% fluorine-containing additive;
[0126] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0127] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0128] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0129] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0130] 3) Add additive F1 to the basic electrolyte obtained in step 2) with a mass fraction of 1 wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 1 wt% F1.
[0131] 4) Assemble sodium / sodium button cells with the sodium secondary battery electrolyte containing 1 wt% F1 obtained in step 3) and place them at 0.5 mA cm -2 Constant current charge-discharge tests were performed at a current density (0.943 mA) to evaluate the cycling stability of sodium ion plating / stripping at both electrodes.
[0132] Example 5
[0133] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0134] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0135] It is composed of 86% organic solvent, 13% electrolyte sodium salt and 1% fluorine-containing additive;
[0136] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0137] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0138] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0139] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0140] 3) Add additive F5 to the basic electrolyte obtained in step 2) with a mass fraction of 1 wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 1 wt% F5.
[0141] 4) Assembling a hard carbon / sodium button cell with the sodium secondary battery electrolyte containing 1 wt% F5 obtained in step 3), and performing a constant current charge and discharge test at a rate of 0.5C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0142] 5) Performing an AC impedance test on the battery that has been cycled to a certain number of times in step 4) to evaluate the effect of the sodium secondary battery electrolyte containing 1 wt % F5 on the battery impedance.
[0143] 6) Conducting a contact angle test on the sodium secondary battery electrolyte containing 1 wt% F5 obtained in step 3) to test the contact angle between the sodium secondary battery electrolyte and the hard carbon electrode. The size of the contact angle can reflect the wettability of the electrolyte on the surface of the hard carbon electrode.
[0144] Example 6
[0145] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0146] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0147] It is composed of 80% organic solvent, 17% electrolyte sodium salt and 3% fluorine-containing additive;
[0148] The organic solvent is a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium bis(fluorosulfonyl)imide, and the fluorine-containing additive is
[0149] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0150] 1) mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0151] 2) Add a predetermined amount of sodium bis(fluorosulfonyl)imide to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0152] 3) Add additive F5 to the basic electrolyte obtained in step 2) with a mass fraction of 3wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 3wt% F5.
[0153] 4) Assembling a hard carbon / sodium button cell with the sodium secondary battery electrolyte containing 3 wt % F5 obtained in step 3), and performing a constant current charge and discharge test at a rate of 0.5 C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0154] 5) Performing an AC impedance test on the battery that has been cycled to a certain number of times in step 4) to evaluate the effect of the sodium secondary battery electrolyte containing 3 wt % F5 on the battery impedance.
[0155] 6) Conducting a contact angle test on the sodium secondary battery electrolyte containing 3 wt % F5 obtained in step 3) to test the contact angle between the sodium secondary battery electrolyte and the hard carbon electrode. The size of the contact angle can reflect the wettability of the electrolyte on the surface of the hard carbon electrode.
[0156] Example 7
[0157] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0158] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0159] It is composed of 86% organic solvent, 13% electrolyte sodium salt and 1% fluorine-containing additive;
[0160] The organic solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium hexafluorophosphate, and the fluorine-containing additive is
[0161] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0162] 1) mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0163] 2) Add a predetermined amount of sodium hexafluorophosphate to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0164] 3) Add additive F5 to the basic electrolyte obtained in step 2) with a mass fraction of 1 wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 1 wt% F5.
[0165] 4) Assembling sodium vanadium phosphate / hard carbon button cells with the sodium secondary battery electrolyte containing 1 wt% F5 obtained in step 3), and performing constant current charge and discharge tests at a rate of 0.1C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0166] Example 8
[0167] This embodiment provides a sodium secondary battery electrolyte and a sodium ion battery.
[0168] (1) The sodium secondary battery electrolyte of this embodiment is composed of the following components in percentage by mass:
[0169] It is composed of 80% organic solvent, 17% electrolyte sodium salt and 3% fluorine-containing additive;
[0170] The organic solvent is a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1, the electrolyte sodium salt is sodium bis(fluorosulfonyl)imide, and the fluorine-containing additive is
[0171] (2) The preparation method of the sodium secondary battery electrolyte and the sodium ion battery of this embodiment is as follows:
[0172] 1) mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1, and stirring until ethylene carbonate (EC) is completely dissolved to prepare a mixed solvent;
[0173] 2) Add a predetermined amount of sodium bis(fluorosulfonyl)imide to the mixed solvent obtained in step 1) to a concentration of 1 mol L -1 , stirring thoroughly until the sodium salt is completely dissolved to obtain a basic electrolyte;
[0174] 3) Add additive F5 to the basic electrolyte obtained in step 2) with a mass fraction of 3wt% of the total mass of the electrolyte, shake or stir evenly until the additive is completely dissolved and then stand for 12 hours to obtain a sodium secondary battery electrolyte containing 3wt% F5.
[0175] 4) Assembling sodium vanadium phosphate / hard carbon button cells with the sodium secondary battery electrolyte containing 3 wt % F5 obtained in step 3), and performing constant current charge and discharge tests at a rate of 0.1C after standing for 12 hours to evaluate the cycle stability of the battery under the influence of the electrolyte.
[0176] Comparative Example 1
[0177] Compared with Example 1, no additive is added to the sodium secondary battery electrolyte of Comparative Example 1, and the remaining operations are the same as those of Example 1.
[0178] Comparative Example 2
[0179] Compared with Example 3, no additive is added to the sodium secondary battery electrolyte of Comparative Example 2, and the remaining operations are the same as those of Example 3.
[0180] Comparative Example 3
[0181] Compared with Example 4, no additive is added to the sodium secondary battery electrolyte of Comparative Example 3, and the remaining operations are the same as those of Example 4.
[0182] test:
[0183] (1) The sodium secondary battery electrolytes obtained in Examples 1 to 2, Examples 5 to 6 and Comparative Example 1 were assembled into hard carbon / sodium button cells. After standing for 12 hours, constant current charge and discharge tests were performed at a rate of 0.5C to evaluate the cycle stability of the battery under the influence of the electrolyte. The results are shown in Table 1:
[0184] Table 1
[0185]
[0186]
[0187] It can be seen from Table 1 that compared with Comparative Example 1 in which no additive is added, Examples 1 to 2 add the additive F1 shown in the present invention to the sodium secondary battery electrolyte, and Examples 5 to 6 add the additive F5 shown in the present invention to the sodium secondary battery electrolyte. The hard carbon / sodium button batteries finally prepared have better cycle stability.
[0188] (2) The contact angle test was performed on the sodium secondary battery electrolytes obtained in Examples 1 to 2, Examples 5 to 6 and Comparative Example 1. The contact angles of the sodium secondary battery electrolytes with the hard carbon electrode were tested. The results are shown in Table 2:
[0189] Table 2
[0190] Test subjects additive Contact angle / ° Comparative Example 1 -- 26.8 Example 1 1wt%F1 26.4 Example 2 3wt%F1 23.0 Example 5 1wt%F5 25.5 Example 6 3wt%F5 22.7
[0191] As shown in Table 2, compared with Comparative Example 1 without adding additives, Examples 1 to 2 add the additive F1 shown in the present invention to the sodium secondary battery electrolyte, and Examples 5 to 6 add the additive F5 shown in the present invention to the sodium secondary battery electrolyte, and the contact angle between the final prepared sodium secondary battery electrolyte and the hard carbon electrode is smaller. Combined with Table 1, it can be seen that the sodium secondary electrolyte of the present invention has a smaller contact angle with the electrode, which can achieve better infiltration of the electrolyte on the surface of the hard carbon electrode. Good wettability ensures sufficient contact between the sodium secondary electrolyte and the electrode, thereby ensuring effective sodium ion transmission and better film formation on the electrode surface, and finally ensuring a reversible sodium ion insertion and extraction process and significantly improved electrochemical performance.
[0192] (3) The sodium secondary battery electrolytes obtained in Examples 3, 7 to 8 and Comparative Example 2 were assembled into sodium vanadium phosphate / hard carbon button cells. After standing for 12 hours, constant current charge and discharge tests were performed at a rate of 0.1C to evaluate the cycle stability of the battery under the influence of the electrolyte. The results are shown in Table 3:
[0193] Table 3
[0194]
[0195] It can be seen from Table 3 that compared with Comparative Example 2 without adding additives, Example 3 adds the additive F1 shown in the present invention to the sodium secondary battery electrolyte, and Examples 7 to 8 add the additive F5 shown in the present invention to the sodium secondary battery electrolyte. The sodium vanadium phosphate / hard carbon button batteries finally prepared have better cycle stability.
[0196] Figure 1 (a) is a comparison chart of the cycle stability of the hard carbon / sodium half-cells prepared in Example 1, Example 2 and Comparative Example 1 of the present invention, Figure 1 (b) is the corresponding coulombic efficiency comparison diagram. The experimental results show that the addition of 1wt% and 3wt% of additive F1 can improve the cycle stability of hard carbon / sodium half-cell in carbonate system, and according to Figure 1 (b) It can be seen that in the later stage of the cycle, 1wt% and 3wt% of additive F1 can make the battery coulombic efficiency more stable. Comprehensive comparison and analysis of the above three cycle performance data show that the optimal concentration of additive F1 is 1wt%.
[0197] Figure 2 This is an impedance comparison diagram of the hard carbon / sodium half-cells prepared in Example 1 of the present invention and Comparative Example 1 after different numbers of cycles (150 cycles, 500 cycles). The experimental results show that the addition of 1wt% additive F1 can delay the impedance increase during the entire battery cycle, which indicates that the additive F1 assists in building a low-impedance electrode / electrolyte interface.
[0198] Figure 3 3 is a comparison chart of the contact angle test results of the sodium secondary battery electrolyte prepared in Example 1, Example 2 and Comparative Example 1 of the present invention. The experimental results show that the addition of additive F1 significantly reduces the contact angle between the electrolyte and the surface of the hard carbon electrode, and significantly improves the wettability of the electrolyte. Good electrolyte wettability promotes rapid sodium ion transmission and better film formation on the surface of the hard carbon electrode. The improvement of these properties is directly related to the better cycle stability of the sodium ion battery.
[0199] Figure 4 It is a comparison chart of the cycle stability of sodium vanadium phosphate / hard carbon full batteries prepared in Example 3 of the present invention and Comparative Example 2 at different rates. The experimental results show that Example 3 has better stability, which is correlated with the results presented by the hard carbon / sodium half-cell. The performance of the full battery at different rates is improved, especially the improvement of rate performance. The main factor is the optimization of the hard carbon negative electrode interface.
[0200] Figure 5It is a comparison chart of the cycle stability of the sodium / sodium symmetrical battery prepared in Example 4 of the present invention and Comparative Example 3. The experimental results show that after adding 1wt% of the additive F1, the overpotential of the symmetrical battery is significantly lower than the overpotential of the battery without adding the additive, indicating that the additive optimizes the electrode / electrolyte interface.
[0201] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0202] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A sodium secondary battery electrolyte, characterized in that Including organic solvents, electrolyte sodium salts and fluorine-containing additives; The fluorine-containing additive is Calculated by mass percentage of the sodium secondary battery electrolyte, the sodium secondary battery electrolyte includes 72% to 92% of an organic solvent, 7% to 23% of an electrolyte sodium salt and 1% to 5% of the fluorine-containing additive.
2. The sodium secondary battery electrolyte according to claim 1, characterized in that Calculated by mass percentage of the sodium secondary battery electrolyte, the sodium secondary battery electrolyte includes 79% to 90% of an organic solvent, 9% to 20% of an electrolyte sodium salt and 1% to 3% of the fluorine-containing additive.
3. The sodium secondary battery electrolyte according to claim 2, characterized in that: The organic solvent is a cyclic carbonate or a linear carbonate, or a mixed solvent consisting of a cyclic carbonate and a linear carbonate.
4. The sodium secondary battery electrolyte according to claim 3, characterized in that: The cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, γ-hydroxybutyrolactone, 4-hydroxy-n-valerolactone and δ-valerolactone; The linear carbonate is selected from at least one of diethyl carbonate, ethyl methyl carbonate and dimethyl carbonate.
5. The sodium secondary battery electrolyte according to claim 4, characterized in that: In the mixed solvent, the volume ratio of the cyclic carbonate to the linear carbonate is (0.8-1.2):
1.
6. The sodium secondary battery electrolyte according to claim 5, characterized in that: The organic solvent is a mixed solvent consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 1:
1.
7. The sodium secondary battery electrolyte according to any one of claims 1 to 6, characterized in that: The electrolyte sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide and sodium trifluoromethylsulfonate.
8. The sodium secondary battery electrolyte according to any one of claims 1 to 6, characterized in that: The concentration of the electrolyte sodium salt in the organic solvent is 0.8 mol / L to 1.5 mol / L.
9. A sodium secondary battery, characterized in that: A sodium secondary battery electrolyte comprising the electrolyte of any one of claims 1 to 8.
10. The sodium secondary battery according to claim 9, characterized in that The sodium secondary battery is a sodium ion battery or a sodium air battery.
Citation Information
Patent Citations
Electrolyte and cell
CN101997139A
Electrolyte and battery using it
CN1622386A
Additives for suppressing dendritic growth in batteries
US10873107B2